A Structure Equation Modeling of Guidelines on Effective Meeting Management in Industrial Business Sector - Sanrach, Raknarin; Silpjaru, Thanin (Applied Science and Engineering Progress, 2020)
The purposes of this research were to investigate guidelines on effective meeting management in different sizes of industrial business corporates, and to develop a structure equation model based on those found guidelines. Quantitative and qualitative research methods were employed in this study. The quantitative data were obtained from interviewing 500 employees responsible for business meeting arrangement. Investigated guidelines on effective meeting management in industrial business sector were of 4 aspects; namely, meeting leader, premeeting operation, meeting operation, and post-meeting operation. Most important guidelines respectively found in each aspect were: punctuality had to be strictly observed, meeting chairperson had to check and recheck the agenda to get ready for the meeting, attendees should honor and respect each other when expressing opinions, and the meeting secretary had to send the minutes of the previous meeting to the participants allowing them to have enough time to consider the resolutions before the next meeting. For the hypothesis testing, it was found that all sizes of industrial business similarly recognized the importance of the guidelines on effective meeting management in the industry sector. The analysis of the developed structure equation model showed that it was in accordance and in harmony with the empirical data and passed the evaluation criteria. Its Chi-square probability level, relative Chi-square, goodness of fit index, and root mean square error of approximation were 0.149, 1.139, 0.970, and 0.017 respectively. The statistical significance of this study was set at 0.05.